Examination of the relation between periodontal health status and cardiovascular risk factors: serum total and high density lipoprotein cholesterol, C-reactive protein, and plasma fibrinogen - Wu, T; Trevisan, M; Genco, R J; Falkner, K L; Dorn, J P; Sempos, C T (American journal of epidemiology, 2000)
Using data from the Third National Health and Nutrition Examination Survey (1988-1994), the authors examined the relation between periodontal health and cardiovascular risk factors: serum total and high density lipoprotein cholesterol, C-reactive protein, and plasma fibrinogen. A total of 10,146 participants were included in the analyses of cholesterol and C-reactive protein and 4,461 in the analyses of fibrinogen. Periodontal health indicators included the gingival bleeding index, calculus index, and periodontal disease status (defined by pocket depth and attachment loss). While cholesterol and fibrinogen were analyzed as continuous variables, C-reactive protein was dichotomized into two levels. The results show a significant relation between indicators of poor periodontal status and increased C-reactive protein and fibrinogen. The association between periodontal status and total cholesterol level is much weaker. No consistent association between periodontal status and high density lipoprotein cholesterol was detectable. Similar patterns of association were observed for participants aged 17-54 years and those 55 years and older. In conclusion, this study suggests that total cholesterol, C-reactive protein, and fibrinogen are possible intermediate factors that may link periodontal disease to elevated cardiovascular risk.